Mathematical models of beams and cables - Luongo, Angelo; Zulli, Daniele; Wiley eBooks (Hoboken : Wiley, 2013)
Nonlinear models of elastic and visco-elastic onedimensional continuous structures (beams and cables) are formulated by the authors of this title. Several models of increasing complexity are presented: straight/curved, planar/non-planar, extensible/inextensible, shearable/unshearable, warpingunsensitive/ sensitive, prestressed/unprestressed beams, both in statics and dynamics. Typical engineering problems are solved via perturbation and/or numerical approaches, such as bifurcation and stability under potential and/or tangential loads, parametric excitation, nonlinear dynamics and aeroelasticity.
A one-dimensional beam metamodel -- Straight beams -- Curved beams -- Internally constrained beams -- Flexible cables -- Stiff cables -- Locally-deformable thin-walled beams -- Distortion-constrained thin-walled beams.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Structural analysis (Engineering) -- Mathematical models; Girders; Cables; Cables; Girders; Structural analysis (Engineering) -- Mathematical models; TECHNOLOGY & ENGINEERING -- Engineering (General); Cables; Girders; Structural analysis (Engineering) -- Mathematical models; Electronic books